Conceptual Framework for the Role of Information and Communication Technology (ICT) in achieving the Sustainable Development Goals - Athurupane, Prabhasara; Wickramsinghe, Bhagya (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
This paper seeks to evaluate the role of ICT in achieving the sustainable development goals adopted by the United Nations in 2015. While SDGs do not specifically address ICT, or include a goal on development of ICT, as argued (Berleur & Avgerou, 2005)in this paper, it is an underlying element embedded in the very concept of sustainable development rooted in the definition as propounded by the Brundtland Report. The objective of this paper is to evaluate whether there is a possibility to develop a conceptual framework to ground the use of ICTs in achieving SDGs. For this purpose, this research has evaluated the common conceptual frameworks developed by scholars and posits that rather than developing an all-encompassing framework, it is possible to identify certain necessary features for the role of the ICTs in achieving SDGs. This approach enables policy and decision makers to look at the role of ICT as an integral component of socio-economic and environmental decision making and implementation.